1995
DOI: 10.1016/0014-5793(95)01094-u
|View full text |Cite
|
Sign up to set email alerts
|

Homodimerization and intermolecular tyrosine phosphorylation of the Tyk‐2 tyrosine kinase

Abstract: The Jak kinases and Stat transcription factors play a major role in signaling of various cytokines including IFNa. In this report we show a ligand-independent interaction between Tyk-2 and Jak-I kinases. We also demonstrate that the Tyk-2 kinase forms a homodimer that has the ability to undergo intermolecular tyrosine phosphorylation. The formation of the Tyk-2 homodimer is independent of both tyrosine phosphorylation and the presence of the tyrosine kinase domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We hypothesize that not only the transmembrane receptor chains but also Jak1, Tyk2 and also RACK-1 need be present in comparable levels for full receptor activity to be observed. Notably, it has been shown that Janus kinases such as Tyk2 and Jak1 interact independantly of receptor activation [42]. A structural model encompassing these requirements is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that not only the transmembrane receptor chains but also Jak1, Tyk2 and also RACK-1 need be present in comparable levels for full receptor activity to be observed. Notably, it has been shown that Janus kinases such as Tyk2 and Jak1 interact independantly of receptor activation [42]. A structural model encompassing these requirements is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated JAK1 interaction partners using JAK1 as the query protein. In this case, the majority of proteins related to JAK1 were kinases, including TYK2 and SYK, which have been demonstrated to interact with JAK1 [ 23 , 24 ]. The most common transcription factor family was the STAT family, which are well-proven substrates for JAK1; STAT1 and STAT5b were the most frequent JAK1 partners in the 4 analyzed datasets [ 25 ] (Additional file 1 : Supplementary material S3).…”
Section: Resultsmentioning
confidence: 99%
“…We expressed V, W, GFP and GFP–Vs in 293FT cells along with FLAG-tagged Jak1 or Tyk2, and looked at interactions between these proteins by two assays: (1) the ability of the viral protein to co-precipitate Jak1 or Tyk2, and (2) the ability of the viral protein to block the autophosphorylation observed when either of these kinases is overexpressed, either transiently or as a transgene. This latter activity can be taken as a model of the ability of a protein to block IFN-stimulated activation of the kinase (Chinnakannan et al , 2013; Domanski et al , 1995; Eilers et al , 1996; Quelle et al , 1995; Valmas et al , 2010). We found that, like the complete V protein, GFP–Vs co-precipitated both receptor-associated kinases, whilst the W domain precipitated neither (Fig.…”
Section: Resultsmentioning
confidence: 99%